2010
DOI: 10.2193/2009-059
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Cause‐Specific Mortality of Corsac and Red Foxes in Mongolia

Abstract: The corsac fox (Vulpes corsac) and red fox (Vulpes vulpes) range widely across northern and central Asia and may be declining in many regions due to overhunting and other causes. However, details of the fundamental causes of survival and mortality of both species remain largely unquantified, but may be crucial for understanding interspecific relationships and developing effective conservation actions. We studied a radiomarked population of sympatric corsac and red foxes in central Mongolia to quantify survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…In a study conducted in Mongolia, the main mortality factors for Corsac Fox were hunting by humans (60%) and predation by other large carnivores (30%) (Murdoch et al, 2010b). Carnivores which potentially could conflict with Corsac Fox in this area are the Grey Wolf (Canis lupus) and Golden Jackal (Canis aureus), although predation by the Golden Eagle is also reported.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study conducted in Mongolia, the main mortality factors for Corsac Fox were hunting by humans (60%) and predation by other large carnivores (30%) (Murdoch et al, 2010b). Carnivores which potentially could conflict with Corsac Fox in this area are the Grey Wolf (Canis lupus) and Golden Jackal (Canis aureus), although predation by the Golden Eagle is also reported.…”
Section: Discussionmentioning
confidence: 95%
“…Murdoch et al (2010b) reported that hedgehogs, Hemiechinus spp., form a very low percentage of Corsac Fox diet and only during a limited period of their life (0.4% in dispersal and 0.7% in breeding). There are few studies on Corsac diet and according to Murdoch et al (2010a) their main food items are insects followed by small mammals.…”
Section: Discussionmentioning
confidence: 99%
“…management activities. For example, red foxes are intensively hunted (illegally) in the reserve during the winter (Murdoch et al, 2010a), and the distribution map shows areas where foxes are most likely to be found. Managers may then choose to focus their patrols on these areas during the hunting season.…”
Section: Discussionmentioning
confidence: 99%
“…However, radio-telemetry and observation data suggest that red foxes select some habitats more frequently than expected suggesting that the species is not uniformally distributed across the country (Murdoch, 2009;Munkhzul et al, 2012). In Ikh Nart, red foxes seem to favor more rugged, rocky terrain and the species is hunted intensively during the winter months (Murdoch et al, 2007;Murdoch et al, 2010a). Toad-headed agamas represent perhaps the most widely distributed reptile in Mongolia and can reach densities that exceed 100 individuals/ha (Rogovin et al, 2001;Murdoch et al, 2010b).…”
Section: Occupancy Modelsmentioning
confidence: 99%
“…In the mid-2000s, research expanded further to include meso-carnivores and their prey that focused primarily on the ecology of red (Vulpes vulpes) and corsac foxes (V. corsac; Murdoch et al, 2010aMurdoch et al, , 2010bMurdoch et al, , 2016Lkhagvasuren et al, 2016), but also gathered data on Pallas' cats (Otocolobus manul) and Asian badgers (Meles leucurus) (Murdoch et al, 2006a;Murdoch & Buyandelger, 2010). The meso-carnivore project also initiated annual monitoring of small mammal and lizard populations (Murdoch et al, 2010c(Murdoch et al, , 2010c.…”
Section: Gathering a Foundation Of Scientific Datamentioning
confidence: 99%